2014
DOI: 10.1017/s1751731114000238
|View full text |Cite
|
Sign up to set email alerts
|

Effects of olive and fish oil Ca soaps in ewe diets on milk fat and muscle and subcutaneous tissue fatty-acid profiles of suckling lambs

Abstract: Enhancing healthy fatty acids (FAs) in ewe milk fat and suckling lamb tissues is an important objective in terms of improving the nutritional value of these foods for the consumer. The present study examined the effects of feeding-protected lipid supplements rich in unsaturated FAs on the lipid composition of ewe milk, and subsequently in the muscle and subcutaneous adipose tissues of lambs suckling such milk. Thirty-six pregnant Churra ewes with their new-born lambs were assigned to one of three experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 34 publications
3
30
1
Order By: Relevance
“…Similar results have been reported by Jenkins (2000) in steers fed with rapeseed oil rich in oleic acid, in which an increase in the t 11-18:1 content from 1.72% to 4.22% was observed. Likewise, Pérez Alba et al (1997) and Gallardo et al (2014) reported a drastic increase in the content of trans-18:1 and t 11-18:1 isomers, respectively, in dairy sheep that were also offered calcium soap of olive oil. However, Hristov et al (2005), in a study comparing sunflower oil rich in linoleic acid (76.5% linoleic acid) and sunflower oil rich in oleic acid (76.5% oleic acid) in concentrate lot steers, found no differences in the content of t 11-18:1 or c 9,t 11-18:2.…”
Section: Meat Qualitymentioning
confidence: 91%
See 1 more Smart Citation
“…Similar results have been reported by Jenkins (2000) in steers fed with rapeseed oil rich in oleic acid, in which an increase in the t 11-18:1 content from 1.72% to 4.22% was observed. Likewise, Pérez Alba et al (1997) and Gallardo et al (2014) reported a drastic increase in the content of trans-18:1 and t 11-18:1 isomers, respectively, in dairy sheep that were also offered calcium soap of olive oil. However, Hristov et al (2005), in a study comparing sunflower oil rich in linoleic acid (76.5% linoleic acid) and sunflower oil rich in oleic acid (76.5% oleic acid) in concentrate lot steers, found no differences in the content of t 11-18:1 or c 9,t 11-18:2.…”
Section: Meat Qualitymentioning
confidence: 91%
“…These isomers could be transferred to milk fat or meat fat. A small number of studies carried out with olive oil in dairy sheep (Pérez Alba et al, 1997;Gómez-Cortés et al, 2008;Gallardo et al, 2014), feedlot lambs ) and suckling lambs (Manso et al, 2011;Gallardo et al, 2014) have reported an increase in oleic acid, a substantial increase in a wide variety of trans-monoene isomers and an increase in c9,t11-18:2 in milk and meat. Spain is the world's most important producer of olive oil, and when it is refined for human consumption a large quantity of by-products are formed, which are often used in animal feeds.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research with dietary n-3 fatty acid sources has focused on changing milk fatty acid composition (Shingfield et al, 2005;Lejonkleva et al, 2013;Nudda et al, 2013;Gallardo et al, 2014), disregarding the effect of n-3 fatty acids on the immune system or oxidative stress in dairy cows. The aim of this research was to determine the influence of dietary replacement of n-6 with n-3 polyunsaturated fatty acids (PUFA) on cellular immunity and oxidative stress in the transition period of dairy cows.…”
Section: Introductionmentioning
confidence: 99%
“…Besides variation in experimental conditions, the large variation in transfer efficiencies between experiments also might be related to differences in protection efficiency, probably induced by variation in production procedures of the Ca salts. Generally, very inconsistent results are found in literature dealing with Ca salts of unsaturated FA, but most of them reported an incomplete protection, supported by the many BH intermediates which were found in milk and/or rumen fluid .…”
Section: Overview Of Existing Rumen Lipid Protection Technologiesmentioning
confidence: 97%